2011
DOI: 10.1097/aln.0b013e318219d74f
|View full text |Cite
|
Sign up to set email alerts
|

Moderate-dose Vasopressin Therapy May Impair Gastric Mucosal Perfusion in Severe Sepsis

Abstract: Background:The effects of moderate-dose vasopressin on gastric mucosal perfusion and its relation to global and hepatosplanchnic hemodynamic and oxygen transport variables were investigated in patients with severe sepsis. Methods: Vasopressin was administered at a dose of 0.04 IU ⅐ kg Ϫ1 ⅐ h Ϫ1 over 4 h in 12 patients with severe sepsis who were receiving norepinephrine. During the study period, the norepinephrine infusion rate was reduced to keep mean arterial blood pressure constant. Hepatosplanchnic blood f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
0
11
0
2
Order By: Relevance
“…So far, few studies indicate that vasopressin decreases mesenteric and splanchnic blood flow. Results from studies in humans reported that vasopressin was responsible for this decreased flow even in the presence of additional catecholamines such as norepinephrine [13,[29][30][31]. Additionally, another interesting study demonstrated that addition of vasopressin resulted in decreased EN tolerability [26].…”
Section: Discussionmentioning
confidence: 99%
“…So far, few studies indicate that vasopressin decreases mesenteric and splanchnic blood flow. Results from studies in humans reported that vasopressin was responsible for this decreased flow even in the presence of additional catecholamines such as norepinephrine [13,[29][30][31]. Additionally, another interesting study demonstrated that addition of vasopressin resulted in decreased EN tolerability [26].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous investigators have shown that the administration of vasopressin to patients in septic shock leads to enteric and gastric hypoperfusion 14 17 . In a porcine surgical model of cardiopulmonary bypass, Bomberg and colleagues reported that vasopressin induced ischemia of the rectosigmoid region.…”
Section: Enteric Effects Of Pressorsmentioning
confidence: 99%
“…En ce qui concerne la microcirculation digestive, dans une autre étude, deux heures après avoir remplacé la noradrénaline par de l'arginine vasopressine (en moyenne 0,47 UI//min) avec un objectif de PAM stable à 70 mmHg, on constate un maintien du débit sanguin hépatosplanch-nique mesuré par la clairance du vert d'indocyanine malgré la baisse de l'index cardiaque, mais une augmentation de la différence artériogastrique du CO 2 (PCO 2gap ), plaidant en faveur d'une altération de la microcirculation avec hétéro-généité de perfusion aux dépens de la muqueuse gastrique [62]. Ces résultats étaient en accord avec ceux de Van Haren et al [63].…”
Section: Effets De La Vasopressine Sur La Microcirculation Chez L'animalunclassified
“…Vasopressine -Remplacement de la noradrénaline avec objectif de stabilité de la PAM à 70 mmHg ; pas de modification de la clairance du vert d'indocyanine, mais aggravation de la PCO 2gap en tonométrie gastrique [62] -Augmentation de la PCO 2gap en ajoutant de la vasopressine à 0,04 UI/h, la PAM augmentant en moyenne à 68 mmHg [63] -Comparaison vasopressine à la noradrénaline, amélioration de la clairance de la créatinine [64] -Comparasion à la noradrénaline : pas de modification de la PCO 2gap et amélioration de la clairance de la créatinine [65] -Choc distributif en post-CEC, ajout de 4 UI/h de vasopressine à noradrénaline vs noradrénaline seule : diminution de la PCO 2gap , mais augmentation des taux de bilirubine [68] -Ajout de vasopressine jusqu'à 4,8 UI/h à de la noradrénaline, augmentation de la PCO 2gap , diminution du flux [69] -Amélioration du débit de filtration glomérulaire chez des patients sans état de choc en post-CEC, mais dégradation de l'oxygénation rénale [70] Terlipressine -Augmentation de la PAM de 65 à 75, pas de modification par rapport à la vasopressine ou la noradrénaline sur l'indice de flux microcirculatoire sublingual [71] -Bolus de 0,5 mg, amélioration des paramètres de flux microcirculatoire sublingual à h6 et de la clairance de la créatinine [61] -Bolus de 1 mg, diminution de la PCO 2gap et augmentation du flux sanguin gastrique [62] Liens d'intérêts : Les auteurs déclarent ne pas avoir de lien d'intérêt.…”
Section: Sepsis Périopératoireunclassified